Through A Water Lens: Governance, Ideas, Change and the RoleThrough A Water Lens: of Research in Water Management - Moench, Marcus (Water Nepal, 2009)
Mr Moench argues that currently dominant concepts of water management poorly reflect the ideas and behavioral foundations of a global society. He believes that substantial work linking 'practical' water management questions to wider work as ideas, knowledge generation and knowledge system is essential to identify points of leverage for responding effectively to the water problems that are emerging across the world. Keywords: governance Water Nepal Vol. 12, No. 1-2, 2006 Page: 5-46